PENYANDERAAN (GIJZELING) SEBAGAI INSTRUMEN MEMAKSA DALAM HUKUM PERPAJAKAN - Fontian Munzil (Program Studi Magister Ilmu Hukum Universitas Islam Nusantara, 2015)
Tax is a compulsory levy for every citizen who governed with legislation which is the basis of taxation. Tax authorities have the authority to use force/actions to be taken to enable the taxpayer topay the tax. Coercion can bedirect ie the seizure and auction of goods or execution of which is called before the execution must be carried out stage as warning, reprimand, installment payment or the tax authorities actively enforced by issuing a forcing letter. Gijzeling will apply with the condition of the taxpayer does not immediately pay off their tax debt whilethe tax authorities have been doing things like letters of reprimand, letters of forced, confiscation. Gijzeling is temporarily restraining the freedom of taxpayers by placing certain somewhere. Gijzeling did not result in the abolishment of tax debt and tax collection due to the cessation of implementation based on tax laws, the tax debt is paid off if already paid or due to expiry. This study will examine the actions of Gijzeling in the enforcement of tax law as a repressive force of law and legal protection of the taxpayers as a tax payment to the Gijzeling -taking attempt. Research Method described by structured research conducted by scientific normative juridical approach, ie legal research to library materials and secondary data from the study of the principles contained in the laws and methods of comparative law. Analysis with descriptive analytical research specifications also conducted to analyze Gijzeling For Forcing Instruments of Taxation Law. The study found Gijzeling in a last-ditchattempt taxation sufficient morally and psychologically for taxpayers who do not have good faith to pay taxes which Gijzeling must be done carefully in accordance withapplicable regulations, because otherwise it would result in excess counter-productive that does not comply with the law. Law Protection of taxpayers regarding the implementation of Gijzeling has been regulated in detail in the form of quantitative and qualitative terms, and go through the other steps first.